2018
DOI: 10.15694/mep.2018.0000143.1
|View full text |Cite
|
Sign up to set email alerts
|

Using the visual arts to teach clinical excellence

Abstract: Introduction:The authors conducted a review of the literature to identify curricula that incorporate the visual arts into undergraduate, graduate, and continuing medical education to facilitate the teaching of clinical excellence. Methods:The authors searched the PubMed and ERIC electronic databases in May 2017, using search terms such as "paintings," "visual arts," and "medical education," along with terms corresponding to previously defined domains of clinical excellence. Search results were reviewed to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…(Launer, 2012) Two recent articles reviewed the literature on the use of arts-based initiatives in the medical curriculum. (Gelgoot, Caufield-Noll and Chisolm, 2018;Taylor, Lehmann and Chisolm, 2018) Both supported the use of the arts and both noted the lack of research with respect to the evaluation of their use and the long-term impact on learners and patients. Such research would certainly be valuable but challenging to conduct because many factors are instrumental in behavioural change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Launer, 2012) Two recent articles reviewed the literature on the use of arts-based initiatives in the medical curriculum. (Gelgoot, Caufield-Noll and Chisolm, 2018;Taylor, Lehmann and Chisolm, 2018) Both supported the use of the arts and both noted the lack of research with respect to the evaluation of their use and the long-term impact on learners and patients. Such research would certainly be valuable but challenging to conduct because many factors are instrumental in behavioural change.…”
Section: Discussionmentioning
confidence: 99%
“…The same articles identified various obstacles or difficulties with incorporating the visual arts in medical education. (Gelgoot, Caufield-Noll and Chisolm, 2018;Taylor, Lehmann and Chisolm, 2018) These included, lack of interest or engagement by learners, because of negative impressions of the arts and, having educators skilled in using the arts. The film The Doctor addresses the same themes as Fildes' painting and they are equally accessible with respect to their themes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gelgoot et al carried out a literature review on this topic and found some promising responses. 2 This included university courses using discussions over paintings as a way of reflecting on topics such as mental illness, doctor-patient relationship, suffering and death. Penn State, Harvard and UT Austin are among the universities incorporating humanities into medical education.…”
Section: The Experiencementioning
confidence: 99%
“…A report of this study is currently under review as a conditionally accepted publication in a peer-reviewed journal, in addition to the two non-BEAM specific literature reviews already published. 13,16 Beyond the capacity for individual skill-building and interior development, BEAM can also act as a reminder of the inherent togetherness of the medical profession; learning makes beginners of us all by forcing us to ask questions, share reflection, and volunteer ideas at the risk of being really heard by those around us. 17 It's all about being open to the unfamiliar; and this, in turn, reflects naturally the vulnerability of the patient confronting the unfamiliar illness, and hence restores a therapeutic alliance to the clinical relationship.…”
mentioning
confidence: 99%